Angular characteristics of multipath propagation in an indoor industrial environment. Issue 7 (30th March 2021) - Bamba, Aliou; Tanghe, Emmeric; Kamagaté, Aladji; Laly, Pierre; Challita, Frédéric; Konaté, Adama; Joseph, Wout; Liénard, Martine; Gaillot, Davy P.
Abstract: The characteristics of multipath components (MPCs) are addressed in an industrial environment at 1.3 GHz by means of measurements with a multidimensional channel sounder. The maximum likelihood estimator, RiMAX, is used to determine the MPCs parameters and takes into account the diffuse scattering. Both line‐of‐sight (LOS) and obstructed LOS (OLOS) scenarios have been considered, along with the four polarization states. We found that the environment is very rich in multipath, that is on average, about 120 (resp. 70) MPCs in LOS (resp. OLOS) scenario due to the presence of several metallic reflectors. The azimuthal angle implies clustering of the MPCs, and therefore, the estimated MPCs are grouped in clusters using the K ‐powers‐means algorithm based on the multipath component distance. In general, one to four clusters are determined with three clusters occurring with the highest probability, regardless of the scenario. Next, the intra‐cluster parameters have been determined, and we show that the root‐mean‐square (rms) delay spread and rms angular spread follow a gamma distribution, regardless of the polarization. The MPC characteristics agree with the results in the literature and can be valuable when deploying a wireless sensor network in industrial environments.